WILDLIFE DEPENDENCY - Mohd Azlan, Jayasilan; Melynda Cheok, Ka Yi; Sally Soo, Kaicheen; YUS AMIRA, YUSAIMI; Wee, Sze Yee (UNIMAS Publisher, Sarawak Energy Berhad and Natural History Publications (Borneo) Sdn. Bhd., 2024)
Wildlife is exploited for a variety of reasons, for instance, economic development, pest control, subsistence and other traditional needs. These usages have often impacted the concerned species, resulting in reduced densities, slow reproduction rates and even extinction. Moreover, increase in human populations, improved hunting techniques and gear, ease of accessibility via road networks and modern transportation, and increased economic benefits have led to increased hunting pressure in many parts of the world.